2018
DOI: 10.1177/1534735418756193
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Exercise Training on Vascular Endothelial Function in Cancer Survivors

Abstract: Cancer and cardiovascular disease (CVD) are leading causes of morbidity and mortality in the United States. Vascular endothelial dysfunction, an important contributor in the development of CVD, improves with exercise training in patients with CVD. However, the role of regular exercise to improve vascular function in cancer survivors remains equivocal. We performed a meta-analysis to determine the effect of exercise training on vascular endothelial function in cancer survivors. We searched PubMed (1975 to 2016)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 58 publications
1
17
0
1
Order By: Relevance
“…Five reviews suggested that a combination of aerobic and resistance training delivered during or after treatment for prostate cancer survivors could be effective in improving cardiorespiratory fitness and peak oxygen capacity, with resistance training demonstrating improvements to muscular strength . Exercise interventions were less effective in improving other markers of cardiovascular health such as lipid profile, blood pressure, glucose, and cardiometabolic risk among men undergoing ADT .…”
Section: Resultsmentioning
confidence: 99%
“…Five reviews suggested that a combination of aerobic and resistance training delivered during or after treatment for prostate cancer survivors could be effective in improving cardiorespiratory fitness and peak oxygen capacity, with resistance training demonstrating improvements to muscular strength . Exercise interventions were less effective in improving other markers of cardiovascular health such as lipid profile, blood pressure, glucose, and cardiometabolic risk among men undergoing ADT .…”
Section: Resultsmentioning
confidence: 99%
“…However, interventions in these studies were heterogeneous and did not often describe the intensity or type of exercise used. A recent meta-analysis suggested that a workload of 600 MET (intensity-minutes) was associated with a clinically significant improvement in fitness capacity, suggesting that a 10-week program of 90 min/week of supervised training at 70% of VO 2peak may be sufficient [ 139 141 ]. Another meta-analysis found that cancer survivors who completed 15 MET-h/week presented a 27% lower risk of cancer mortality with respect to controls, and this effect was greater in patients who were sedentary at pre-diagnosis (35% lower risk) [ 142 ].…”
Section: Exercise-oncology: a Pragmatic Point Of View For Cliniciansmentioning
confidence: 99%
“…Thus, ED may contribute to limiting blood flow and perfusion of organs and systems. In addition, this complication is of great clinical importance, since it is an initial reversible stage in the development of atherosclerosis [15]. It is proved that ED is the result of endothelium damage, leading to inflammation, activation of endothelial cells, transcription and synthesis of de novo proteins, including adhesion molecules, cytokines, chemokines and procoagulants [16].…”
Section: Ed and Prognostic Significance Of Et-1 Levelsmentioning
confidence: 99%